Do Currículo Oficial Do Estado De São Paulo Ao Currículo+: O (Multi) Letramento Digital Na Formação Dos Professores De Língua Inglesa Do Ensino Médio - Nogueira, Silvia Cristina Gomes [UNIFESP] (2017)
This research is an educational case study and uses a qualitative approach to analyze in which ways high school English teachers of public schools in the State of São Paulo – Brazil manage to apply in their classes the knowledge built during the courses offered by the State’s Education Department and by its Pedagogic Hubs. These courses involve educational technology and the “Plataforma Currículo+” [Syllabus+ Platform]. The study focuses on whether “From São Paulo’s Official Syllabus to Currículo+: foreign language teachers in a time of authorship” (a course offered by an administrative unit in the city of São Paulo’s eastern district) has contributed in any way to rethink teaching practices regarding the use of digital information technologies (DIT), particularly the digital learning objects (DLO) of Plataforma Currículo+. The changes we look for are those of a critical-reflexive nature, so as to enable a Freirean empowerment of the teachers via an authorial perspective. This research seeks to learn: a) which strategies are being used by high school English teachers to cope with infrastructure problems that hinder the use of technological resources; b) in what ways are DLO being used in high school English classes; c) whether the didactic sequences produced by the teachers during the aforementioned course have been applied with their students, and which difficulties arose then; d) how did the teachers interviewed for the study evaluate the insertion of DLO in their teaching practices. The theoretical framework encompasses the following conceptual areas: 1) continued teacher formation; 2) technology in education; 3) cyberculture; 4) teachers’ digital literacy and multiliteracy from a non-instrumental standpoint, so that the teachers’ digital literacy may foster their students’. To that end, we analyze the following data: the State of São Paulo’s Official Syllabus inauguration document, the legal document that instates the Program New Technologies – New Possibilities, umbrella program to Currículo+; the Didactic Sequences produced by our three research subjects, as well as a content analysis of the subjects’ reports on the aforementioned course (“From São Paulo’s Official Syllabus…”). We have found that, despite the many fragilities in the infrastructure of public schools in the State of São Paulo, the interviewed teachers have managed, by a combination of creativity, the collaboration of their superiors and teamwork between colleagues, to successfully introduce DIT into their teaching practices. Our findings also reveal that a) as long as there is planning and well-defined goals, DLO can contribute to student learning; b) the authorship tools available at the Plataforma Currículo+ enable students to build knowledge, provided there is planning and mediation on their teachers’ part during the process.